PERFORMANCE OF THE STATE CIVIL APPARATUS (ASN) AT THE TANAH DATAR REGENCY INSPECTORATE: OVERVIEW OF PERFORMANCE IN MINANGKABAU CULTURE, INDONESIA - Sri Adella Fitri; Mega Rahmi; M. Tri Rahmat Fajri (Indonesian Journal of Multidisciplinary Science, 2022)
The problem of state civil servants (ASN) performance is an interesting issue to be discussed, and the development of various assessment methods have been unable to cause major improvements. The supervision carried out by the inspectorate is a performance indicator in carrying out their duties. Furthermore, the achievement depicted in the work ethics has become a Minangkabau culture and has been rooted in the values of life. This research used a mixed method with a survey approach, through the distribution of questionnaires to a sample of 42 ASN of Tanah Datar Regency Inspectorate. The results showed a significant positive effect of training (X1) and motivation (X2) on performance (Y). Simultaneously, there is a significant positive effect of variables (X1) and (X2) on employee performance (Y). The joints of life in Minangkabau culture have been regulated through the philosophy of life and have become the order of living by the community. The culture touches all aspects of life, including educational and performance values, as well as self-motivation, which are still maintained at work.